Policy Perspectives on Water Management for Resilient Agri-food Systems in Southwest Coastal Bangladesh - Rahman, M. Mokhlesur; Sarker, Mou Rani (CGIAR System Organization, 2024)
Access to reliable water is vital for sustaining agri-food systems, yet its equitable distribution faces mounting challenges from climate change, rising sectoral demands, and upstream water withdrawals. Water management is further complicated by diverse social, policy, and institutional drivers, and limited understanding of social-ecological dynamics impeding effective collaboration among sectors, stakeholders, and grassroots communities. National policies play a crucial role in governing water resources, underscoring the need for a comprehensive analysis of sectoral policies to evaluate their effectiveness in fostering an enabling policy environment. This study examines 13 water-food sectoral policies in Bangladesh to identify gaps and propose actionable recommendations for creating a cohesive policy framework that ensures water availability, enhances accessibility, and supports the transformation and resilience of food systems.